Retroperitoneal coelomic cysts - Calvelo, Agustín A.; Mazza, Milton; Noguiera, Alejandro; Falconi, Luis (Cirugía del Uruguay, 1978)
The authors report two cases of meso·colonic retroperitoneal cysts treated by excision. Clinical, biological and radiographic considerations in view of its benignity are confirmed by its histologic diagnosis. The surgical ablation is the only satisfactory method of treatment.